Velocity Analysis of a Slider Crank Mechanism for Delta Robot Arm Manipulation: A Computational Approach (British Journal of Multidisciplinary and Advanced Studies, 2025)
In this research, a velocity analysis of the slider crank mechanism's (SCM) for the delta robot arm manipulation was carried out. For the slider crank mechanism, new velocity response models were created. Trigonometric and inverse trigonometric functions are used in the novel Akozietic mathematical method, which is appropriate for kinematic analysis of intricate mechanisms like the four-bar mechanism (slider crank). The equilibrium conditions of the forces in a four-bar mechanism are used in the Akozietic mathematical technique to create simple mathematical models that enable user-written computer programs in Matlab and other programming languages. According to the velocity profile, the mechanism is under the most stress when the crank angle exceeds 300°, and the velocity is lowest at 180° and 0°.The crank angles where the slider shifts direction are the locations where the velocity passes zero. The novel mathematical procedure created in this study outperformed the other two kinematic analysis methods that were currently in use, according to a comparison of spreadsheets and this new mathematical method for mechanism analysis (Akozietic) with standard numerical solutions completed in Mathematica.